"Balaam's Ass": Smerdyakov as a paradoxical redeemer in Dostoevsky's The Brothers Karamazov. (December 2014) - Cohen, Sharon
Smerdyakov, the likely fourth brother—a bastard, an epileptic, a murderer, a suicide—is glaringly excluded from the tripartite Karamazov soul of the appetitive Dmitri, the rational Ivan, and the spiritual Alyosha. But to dismiss him as an inexplicable freak of nature is to dismiss the entire sobornost, or spiritual community, of Dostoevsky's Brothers Karamazov . This paper carefully examines the character of Smerdyakov, and argues that his willful self-denial of all aspects of life and humanity—his tripartite rejection of the Karamazov soul—culminates in the murder of his father Fyodor. However, I also maintain that Smerdyakov serves as Dostoevsky's warning to Russia's next generation of "gentlemen, " for this "Balaam's ass" will give Russia occasion to reorient and restore her fracturing soul.